2017
DOI: 10.1002/ca.22871
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wrist posture, grip type, and grip force on median nerve shape and cross‐sectional area

Abstract: During grasping, the median nerve undergoes mechanical stress in the carpal tunnel which may contribute to carpal tunnel syndrome. This study investigated the effects of wrist posture, grip type, and grip force on the shape and cross-sectional area of the median nerve. Ultrasound examination was used to obtain cross-sectional images of the dominant wrist of 16 healthy subjects (8 male) at the proximal carpal tunnel during grasping. The cross-sectional area, circularity, and axis lengths of the median nerve wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…Regardless of the method used, there is mixed evidence for the correlation between measures of median nerve circularity and finger positions. Cowley and colleagues 15 noted a slight, nonsignificant decrease in median nerve circularity from 0.57 to 0.54 when the hand was in a neutral position versus a pinching position. Using the reciprocal formula, Yoshii and colleagues 19 found a nonsignificant change in nerve circularity that increased from 1.69 to 1.75 when measured in full finger extension to full finger flexion.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Regardless of the method used, there is mixed evidence for the correlation between measures of median nerve circularity and finger positions. Cowley and colleagues 15 noted a slight, nonsignificant decrease in median nerve circularity from 0.57 to 0.54 when the hand was in a neutral position versus a pinching position. Using the reciprocal formula, Yoshii and colleagues 19 found a nonsignificant change in nerve circularity that increased from 1.69 to 1.75 when measured in full finger extension to full finger flexion.…”
Section: Discussionmentioning
confidence: 97%
“…While we explored the usefulness of these shape categorizations for concurrent measures of circularity, we found that subjective categorization provided additional information related to nerve compression. As sonography is being increasingly used to identify risk factors contributing to median nerve injury 15 and for diagnosis of carpal tunnel syndrome, 22,23 these findings may be useful for advancing both research and practice. Circularity is a quantitative method to identify the roundness of an object in a 2D plane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the recent literature that employed ultrasound to study the effect of wrist angle on peripheral nerves at the wrist have focussed on the median nerve in the carpal tunnel . This prior research has extended the knowledge base documenting that the neutral wrist position caused lower compression of the median nerve in the carpal tunnel than with flexion or extension .…”
Section: Introductionmentioning
confidence: 99%